Exploring spiritual health practitioners' roles and activities in critical care contexts. Issue 1 (2nd January 2022) - Roze des Ordons, Amanda L.; Stelfox, Henry T.; Sinuff, Tasnim; Grindrod-Millar, Kathleen; Sinclair, Shane
Abstract: Family members of patients admitted to the intensive care unit (ICU) experience multidimensional distress. Many clinicians lack an understanding of spiritual health practitioners' role and approaches to providing spiritual support. Through semi-structured interviews and focus groups with 10 spiritual health practitioners, we explored how spiritual health practitioners support families of patients in the ICU to better understand their scope of practice and role within an interdisciplinary critical care team. Spiritual health practitioners' work was described through clinical roles (family support, clinician support, bridging family members and clinicians), activities (companioning, counseling, facilitating difficult conversations, addressing individual needs), tensions (within and between roles and activities, navigating between hope and anticipated clinical trajectory, balancing supportive care and workload) and foundational principles (holistic perspective, resilience). A more comprehensive understanding of these roles and skills may enable clinicians to better integrate spiritual health practitioners into the fabric of care for patients, families, and clinicians themselves.